Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Ii Dan Teknik Peta Pikiran Terhadap Hasil Belajar Siswa Kelas X Sma Negeri 3 Poso Pada Mata Pelajaran Biologi - Dewi Purwasi Samaela; Mohamad Jamhari; I Nengah Kundera (Universitas Tadulako, 2017)
The research was aimed to describing the influence of Jigsaw II type as cooperative learning model and mind mapping technique on the learning achievement for biology subject at grade X, and than to describing the influence of Jigsaw II type as cooperative learning model and mind mapping technique simultaneosly on the learning achievement. The research was quantitative with quasi- experimental design. Population in this research were all students in grade X SMAN 3 Poso which consists of 8 study groups. Research sample that is graders XD and XH, taken with random probabiliy sampling. Research data were obtained from the student achievement, and were analized by t-test was followed by ANOVA test with SPSS 20. The result of the research showed that there was a significant influence jigsaw II type as cooperative learning model and mind mapping technique on the learning achievement for biology subject, and there is significant influence of Jigsaw II type as cooperative learning model and mind mapping technique simultaneosly against on the learning achievement for biology subject. The Conclusion of this research that there is significant influence of jigsaw II type as cooperative learning model and mind mapping technique on the learning achievement for biology subject at grade Xof class X SMAN 3 Poso.